Nitrate framework directive and cross compliance: two case studies from the MO.NA.CO. monitoring network - Speroni, Marisanna; Bazzoffi, Paolo; Borrelli, Lamberto; Bruni, Antonio; Brusa, Gianluca; Cabassi, Giovanni; Capelletti, Maurizio; Carè, Sara; Degano, Luigi; Fucella, Roberto (Italian Journal of Agronomy, 2016)
The Act A4 refers to Articles 4 and 5 of Directive 91/676 / EEC concerning the protection of waters against pollution caused by nitrates from agricultural sources. The A4 Act applies to farms that have land within a Nitrate Vulnerable Zone (NVZ); it also applies to farms, with or without herds, that participate in measure 214 of the Rural Development Plans. The monitoring was performed in two experimental farms belonging to CREA-FLC. Both monitoring sites are located in vulnerable areas designated by the Lombardy Region. In the monitoring period MO.NA.CO., the regional standard of reference were the Decrees of the Regional Government DGR5868 / 2007 and DGR2208 / 2011. The average cost attributable to administrative requirements was about € 600 / year / company and was mainly due to a professional agronomist who prepared the Agronomic Utilization Plan (PUA), assisted the farm in preparing its communication, provided advice and informed farm managers on regulatory updates. An informal, not systematic survey made possible to detect that the cost to fulfil the obligations of communication can be very variable depending on the farm’s characteristics (size, production, size of the herd) and the type of consultant assisting the breeder (freelancer, association, cooperative). For example, in some cases the cost is based on the area of the farm, in others on the number of animals in the herd; and in other situations, the associations and freelance agronomist apply a flat rate for the compilation of the PUAs which is unaffected by farm characteristics and ranging from a minimum of € 100 / year / company practiced by some farmers’ association to a maximum of € 800 / year / company required by some freelance agronomist. At Baroncina farm the storage capacity of the slurry, during the monitoring period, was not compliant with the law because the volumes produced could not be stocked for 120 days as required by the standard. New storage facilities have been designed and built; the overall cost of implementation of new tanks was about € 50 / m3.